2020
DOI: 10.3390/molecules25215045
|View full text |Cite
|
Sign up to set email alerts
|

Wine Intake in the Framework of a Mediterranean Diet and Chronic Non-Communicable Diseases: A Short Literature Review of the Last 5 Years

Abstract: Dietary habits are a determining factor of the higher incidence and prevalence of chronic non-communicable diseases (NCDs). In the aim to find a possible preventive and intervention strategy, the Mediterranean diet (MedDiet) has been proposed as an effective approach. Within the MedDiet, moderate wine consumption with meals is a positive item in the MedDiet score; however, recent studies have reported a dose-response association between alcohol consumption and higher risk of a large number of NCDs. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 126 publications
(177 reference statements)
1
23
0
Order By: Relevance
“…A reduced TRAP immunolabeled cells are noted in the R+Q group. be made at this time (Minzer et al, 2020). Furthermore, excessive alcohol consumption is well known as a major public health concern (Ventura-Cots et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced TRAP immunolabeled cells are noted in the R+Q group. be made at this time (Minzer et al, 2020). Furthermore, excessive alcohol consumption is well known as a major public health concern (Ventura-Cots et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Albeit a recent study of the Global Burden of Disease reported the impact of alcohol consumption (measured as harmonized exposure to one standard drink) on disability-adjusted life years and number of deaths, it fails discriminating type of alcohol, frequency (i.e., once per day vs. seven drinks in a day over a week), and occasion (i.e., during meals vs. overnight) [ 53 ]. There is a long tradition supporting the moderate consumption of alcohol (especially red wine) in the context of healthy dietary patterns, such as the Mediterranean diet [ 14 ], while scientific evidence from meta-analyses shows a clear J-curve association with risk of cardiovascular disease and mortality [ 54 , 55 , 56 ]. Alcohol consumption is strongly affected by the cultural heritage of a population, thus it is not surprising, although it is partially in contrast with the literature, that in the present study the intake of red wine, beer, and white wine (to a lesser extent), have been found to be associated with lower odds of some of the metabolic outcomes investigated.…”
Section: Discussionmentioning
confidence: 99%
“…At least part of these potential effects have been attributed to its content in resveratrol, a polyphenol compound belonging to the stilbenes group, which has been shown to have anti-diabetic, anti-hypertensive, and blood lipid-lowering properties, especially in laboratory studies [ 9 , 10 ], while other evidence has been drawn in a human clinical setting [ 11 , 12 , 13 ]. Furthermore, several studies have demonstrated the favorable effects of white wine intake toward cardiovascular health through modulation of oxidative stress and metabolic biomarkers [ 14 ]. However, similar associations with decreased risk of cardiovascular disease have been reported for other alcoholic beverages as well, including beer and spirits, opening the question as to whether other polyphenol groups might have the same effects, or if alcohol content might be responsible for the aforementioned observational findings.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are represented by flavonols (quercetin and myricetin), chalcones, flavononols, flavanols (catechin and epicatechin), flavones, anthocyanidins and isoflavonoids. Non-flavonoids are represented by phenolic acids, stilbenes (resveratrol), coumarins, lignans, and tannins [ 25 , 26 ]. Most of these compounds have demonstrated some or all of these desired effects: antioxidant, anti-inflammatory, anti-cancer, and anti-microbial ( Figure 1 ) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%